Detection of Volatile Organic Compounds as Potential Novel Biomarkers for Chorioamnionitis – Proof of Experimental Models - Goedicke-Fritz, Sybelle; Werner, Thomas; Niemarkt, Hendrik J.; Wolfs, Tim G. A. M.; Baumbach, Jörg Ingo; Kemp, Matthew W.; Jobe, Alan H.; Rogosch, Tobias; Bous, Michelle; Kaiser, Elisabeth; Stutz, Regine; Meyer, Sascha; et al. (Frontiers in Pediatrics, 2021)
Background: Histologic chorioamnionitis is only diagnosed postnatally which prevents interventions. We hypothesized that volatile organic compounds (VOCs) in the amniotic fluid might be useful biomarkers for chorioamnionitis and that VOC profiles differ between amnionitis of different origins. Methods: Time-mated ewes received intra-amniotic injections of media or saline (controls), or live Ureaplasma parvum serovar 3 (Up) 14, 7 or 3d prior to c-section at day 124 gestational age (GA). 100 μg recombinant ovine IL-1α was instilled at 7, 3 or 1d prior to delivery. Headspace VOC profiles were measured from amniotic fluids at birth using ion mobility spectrometer coupled with multi-capillary columns. Results: 127 VOC peaks were identified. 27 VOCs differed between samples from controls and Up- or IL-1α induced amnionitis. The best discrimination between amnionitis by Up vs. IL-1α was reached by 2-methylpentane, with a sensitivity/specificity of 96/95% and a positive predictive value/negative predictive values of 96 and 95%. The concentration of 2-methylpentane in VOCs peaked 7d after intra-amniotic instillation of Up. Discussion: We established a novel method to study headspace VOC profiles of amniotic fluids. VOC profiles may be a useful tool to detect and to assess the duration of amnionitis induced by Up. 2-methylpentane was previously described in the exhalate of women with pre-eclampsia and might be a volatile biomarker for amnionitis. Amniotic fluids analyzed by ion mobility spectrometry coupled with multi-capillary columns may provide bedside diagnosis of amnionitis and understanding inflammatory mechanisms during pregnancy.